Reconstitution of Platelet Glycoprotein Ib-IX Complex in Phospholipid Bilayer Nanodiscs() - Yan, Rong (2011)
Glycoprotein (GP)Ib-IX complex expressed on platelet plasma membrane is involved in thrombosis and hemostasis by initiating platelet adhesion to von Willebrand factor (VWF) exposed at the injured vessel wall. While most of the knowledge for GPIb-IX is obtained from studies on platelets and transfected mammalian cells expressing GPIb-IX, there is not an in vitro membrane system that allows systematic analysis of this receptor. The phospholipid bilayer Nanodisc composed of a patch of phospholipid surrounded by membrane scaffold protein is an attractive tool for membrane protein study. We show here that GPIb-IX purified from human platelets has been reconstituted into the Nanodisc. Nanodisc-reconstituted GPIb-IX was able to bind various conformation-sensitive monoclonal antibodies. Furthermore, it bound to VWF in the presence of botrocetin with an apparent K(d) of 0.73 ± 0.07 nM. The binding to VWF was inhibited by anti-GPIbα antibodies with epitopes overlapping with the VWF-binding site, but not by anti-GPIbβ monoclonal antibody RAM.1. Finally, Nanodisc-reconstituted GPIb-IX exhibited similar ligand-binding activity as the isolated extracellular domain of GPIbα. In conclusion, GPIb-IX in Nanodiscs adopts native-like conformation and possesses the ability to bind its natural ligands, thus making Nanodisc a suitable in vitro platform for further investigation on this hemostatically important receptor complex.